Potential mechanisms of non-suicidal self-injury (NSSI) in major depressive disorder: a systematic review - Tifei Yuan; Jinghong Chen; Huifeng Zhang; Daihui Peng; Yuqi Cheng; Baichuan Wu; Jiaye Chen; Zhifen Liu (General Psychiatry, 2023)
Background Non-suicidal self-injury (NSSI) is a frequent and prominent phenomenon in major depressive disorder (MDD). Even though its prevalence and risk factors are relatively well understood, the potential mechanisms of NSSI in MDD remain elusive.Aims To review present evidence related to the potential mechanisms of NSSI in MDD.Methods According to Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines, articles for this systematic review were searched on Medline (through PubMed), Embase (through Elsevier), PsycINFO (through OVID) and Web of Science databases for English articles, as well as China National Knowledge Infrastructure (CNKI), SinoMed, Wanfang Data, and the Chongqing VIP Chinese Science and Technology Periodical (VIP) Databases for Chinese articles published from the date of inception to 2 August 2022. Two researchers (BW, HZ) independently screened studies based on inclusion and exclusion criteria and assessed their quality.Results A total of 25 157 studies were searched. Only 25 of them were ultimately included, containing 3336 subjects (1535 patients with MDD and NSSI, 1403 patients with MDD without NSSI and 398 HCs). Included studies were divided into 6 categories: psychosocial factors (11 studies), neuroimaging (8 studies), stress and hypothalamic-pituitary-adrenal (HPA) axis (2 studies), pain perception (1 study), electroencephalogram (EEG) (2 studies) and epigenetics (1 study).Conclusions This systematic review indicates that patients with MDD and NSSI might have specific psychosocial factors, aberrant brain functions and neurochemical metabolisms, HPA axis dysfunctions, abnormal pain perceptions and epigenetic alterations.